2012
DOI: 10.5560/znc.2012.67c0039
|View full text |Cite
|
Sign up to set email alerts
|

The Saponin-Rich Fraction of a Gymnema sylvestre R. Br. Aqueous Leaf Extract Reduces Cafeteria and High-Fat Diet-Induced Obesity

Abstract: We examined the antiobesity effect of a saponin-rich fraction of a Gymnema sylvestre R. Br. aqueous leaf extract (SGE) using cafeteria and high-fat diet-induced obese rats for a period of eight weeks. SGE was orally administered at a dose of 100 mg/kg body weight once a day to the treatment group. It signifi cantly decreased the body weight, food consumption, visceral organs weight, and the levels of triglycerides, total cholesterol, low-density lipoproteins, very low-density lipoproteins, atherogenic index, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Characterization of alcoholic extracts of GS yielded a group of low molecular weight compounds called saponin glycosides (Ahamad, Amin, & Mir, ; Ali Ahmed, Rao, & Rao, ; Dateo & Long, ; Fabio, Romanucci, De Marco, & Zarrelli, ; H. M. Liu, Kiuchi, & Tsuda, ; Murakami et al, ; Rao & Sinsheimer, ; E. R. Shanmugasundaram, Venkatasubrahmanyam, Vijendran, & Shanmugasundaram, ; Sinsheimer & McIlhenny, ; Sinsheimer & Rao, ; Sinsheimer, Rao, & McIlhenny, ; Zhang et al, ; Zhu et al, ). Although several studies have attributed the antidiabetic effect of GS to these chemicals (Baskaran, Kizar Ahamath, Radha Shanmugasundaram, & Shanmugasundaram, ; Di Fabio, Romanucci, Zarrelli, Giordano, & Zarrelli, ; Fabio et al, ; Fushiki, Kojima, Imoto, Inoue, & Sugimoto, ; Kumar et al, ; Murakami et al, ; Reddy, Latha, Vijaya, & Rao, ; Sathya, Kokilavani, & Gurusamy, ; Sugihara et al, ), we suggest that the active constituents in OSA® extract are different. Thus, OSA® was prepared by a molecular weight cutoff isolation procedure that allows exclusion of the majority of low molecular weight saponin constituents and retention of high molecular weight (at least 3 kDa) compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of alcoholic extracts of GS yielded a group of low molecular weight compounds called saponin glycosides (Ahamad, Amin, & Mir, ; Ali Ahmed, Rao, & Rao, ; Dateo & Long, ; Fabio, Romanucci, De Marco, & Zarrelli, ; H. M. Liu, Kiuchi, & Tsuda, ; Murakami et al, ; Rao & Sinsheimer, ; E. R. Shanmugasundaram, Venkatasubrahmanyam, Vijendran, & Shanmugasundaram, ; Sinsheimer & McIlhenny, ; Sinsheimer & Rao, ; Sinsheimer, Rao, & McIlhenny, ; Zhang et al, ; Zhu et al, ). Although several studies have attributed the antidiabetic effect of GS to these chemicals (Baskaran, Kizar Ahamath, Radha Shanmugasundaram, & Shanmugasundaram, ; Di Fabio, Romanucci, Zarrelli, Giordano, & Zarrelli, ; Fabio et al, ; Fushiki, Kojima, Imoto, Inoue, & Sugimoto, ; Kumar et al, ; Murakami et al, ; Reddy, Latha, Vijaya, & Rao, ; Sathya, Kokilavani, & Gurusamy, ; Sugihara et al, ), we suggest that the active constituents in OSA® extract are different. Thus, OSA® was prepared by a molecular weight cutoff isolation procedure that allows exclusion of the majority of low molecular weight saponin constituents and retention of high molecular weight (at least 3 kDa) compounds.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo anti-obesity activity was also observed for the saponin fraction isolated from Gymnema sylvestre R. Br. aqueous leaf extract [70]. The sample was administered to high-fat diet-induced obese rats at a dose of 100 mg/kg body weight for eight weeks.…”
Section: Other Saponin Containing-fractions Affecting Weight Reducmentioning
confidence: 99%
“…It is also a folklore medicine in India used for the treatment of malaria, hyperglycemia, mosquito and snake bites [3]. Pharmacological studies showed that G. sylvestre has hypoglycemic [4,5], anti-caries [6,7] and weight reducing [8,9,10] effects. Triterpenoids [11,12,13,14,15,16,17,18], cyclitols [19], flavonoids [20], peptides [21], pectin [22] and alkaloids [23,24] have been isolated from this plant.…”
Section: Introductionmentioning
confidence: 99%